Des lieux autres pour un autre tourisme ? Les espaces du tourisme gay - Emmanuel Jaurand (Bulletin de l’Association de Géographes Français)
Gay tourism is a recent form of tourism that is part of a community and identity logic. The choice of destinations, accommodation structures and activities is directly linked to being gay, that is to say, to assuming an individual and collective male homosexual identity. The search for safety in relation to homosexuality and the possibility to meet other male homosexuals largely explain the geography of gay tourism. The geography of gay tourism shows a rather limited number of destinations, with large contrasts in their division at a global scale, and the importance of large cities and coastal resorts. The age of these tourist destinations and the question of the relationship to otherness in the place, through the presence of other tourists or the gay or ordinary image of the place, are at the base of a typology of places of gay tourism, which shows a relative variety of situations. Part of the destinations of gay tourism is constituted by places of mass tourism, which can be described as ordinary.